Perbandingan karakteristik pektin kulit buah kakao dan kulit buah kopi dalam sediaan cangkang kapsul - Diar Herawati Effendi; Nety Kurniati; Afnan Syihabuddin; Salma Shofa (STIKes Surya Global Yogyakarta, 2022)
Cocoa peels and coffee peels as food industry have low economic value but have great potential because of the high levels of pectin in them. This research used microwave assistant extraction (MAE) method from kako peel and coffee peel waste and has assessed their potential as a source of raw material for capsule shells. This research included observing the optimization of pectin extraction techniques, standardizing pectin, and observing the quality of the resulting capsule shells. The pectin used comes from cocoa peel and coffee peel waste in West Java. The test results showed that the quality of the pectin obtained from cocoa shells and coffee husks complied with IPPA (International Pectin Produce Association) standards so that these pectins could be used for industrial purposes. While the capsule shells obtained have met the organoleptic standards and the disintegration time of the capsule shells according to the Indonesian Pharmacopoeia. Some of the parameters that meet these standards were the size of the capsule shell, both the uniformity of the size of the capsule cap, the uniformity of the size of the capsule body and the minimum disintegration time. Meanwhile, the weight uniformity standards have not met the requirements. The coffee peel capsule shells also meet the Indonesian Pharmacopoeia standards in terms of uniformity of capsule cap size, uniformity of capsule body size, minimum disintegration time, and uniformity of weight. In addition, capsule shells made from cocoa peel and coffee peel meet the requirements for the characteristics of good capsule shell materials where the results of the elongation strength and tensile strength tests meet the quality requirements. So it can be seen that the pectin from cocoa and coffee peels waste have good character to be developed as a source of pectin for pharmaceutical raw materials with the addition of other excipients, such as CMC-Na and carrageenan